1987
DOI: 10.1021/bi00386a038
|View full text |Cite
|
Sign up to set email alerts
|

Locus of a histidine-based, stable trifunctional, helix to helix collagen cross-link: stereospecific collagen structure of type I skin fibrils

Abstract: The loci of the three amino acid residues that contribute their prosthetic groups to form the stable, nonreducible, trifunctional intermolecular cross-link histidinohydroxylysinonorleucine in skin collagen fibrils were identified. Two apparently homogeneous three-chained histidinohydroxylysinonorleucine cross-linked peptides were chromatographically isolated. They were obtained from a tryptic digest of denatured unreduced 6 M guanidine hydrochloride insoluble bovine skin collagen. Amino acid and sequence analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…Although type I collagen is also found in large quantities in soft tissues, the structure of its mature crosslinks e.g. in skin differs from that in bone (Mechanic et al, 1987). Thus it is likely that skin collagen degradation does not lead to liberation of antigens reacting in the ICTP assay.…”
Section: Discussionmentioning
confidence: 99%
“…Although type I collagen is also found in large quantities in soft tissues, the structure of its mature crosslinks e.g. in skin differs from that in bone (Mechanic et al, 1987). Thus it is likely that skin collagen degradation does not lead to liberation of antigens reacting in the ICTP assay.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrrolidine rings of proline and hydroxyproline impose restrictions on the conformation of the polypeptide chain and help to strengthen the triple helix (Bae et al 2008). Hydroxylysine of 4-6 residues/1,000 residues was found in both collagens, suggesting the partial cross-linking of collagen via covalent bond (Mechanic et al 1987). Therefore, collagen from C. catla and C. mrigala might have the different molecular properties from that of other species due to the difference in imino acid content and cross-linking.…”
Section: Amino Acid Analysismentioning
confidence: 94%
“…The low hydroxylation level of the telopeptides was further substantiated by the observed 5-fold elevation over normal levels for LNL, a crosslink derived from telopeptide lysyl residues. The presence of the allysine crosslinking pathway in BS bone was not accompanied by maturation to the nonreducible crosslink histidinohydroxylysinonorleucine (HHL) as in skin and cornea collagen (10)(11): only marginal amounts of HHL were detected in affected bone (Ͻ0.05 HHL͞triple helix). Pyridinium crosslink levels in bone of patient 3 showed, like patient 505 and 507, a 10-fold decrease compared with control bone (data not shown); other crosslinks were not determined.…”
Section: Analysis Of Bs Bone Collagenmentioning
confidence: 99%
“…More than ten different collagen crosslinks are known; their structure, number, and location are highly tissue specific and not related to a specific collagen type (4)(5)(6)(7)(8). Stereochemical and x-ray diffraction studies revealed that differences in molecular packing of collagen within fibrils are associated with differences in crosslink profiles (9)(10)(11)(12). Proper mineralization probably depends on a correct alignment of collagen molecules, as nucleation of calcium apatite crystals starts in the gap region, i.e., in the area adjacent to the crosslink site (9).…”
mentioning
confidence: 99%